Discrete Dynamical System generated by set-valued function in metric spaces - Muslikh, Mohamad; Fitri, Sa'adatul (Jurnal Matematika Integratif, 2024)
The main purpose of this article is to study the behavior of the solutionsof discrete dynamical systems generated by set-valued mapping. Moreprecisely, we study the existence of convergence iterations in the presence of computational errors for set-valued mapping. Then a necessarycondition shows the existence and uniqueness of a fixed point for theset-valued maps.